Secondary battery and electric device

By using a combination of lithium-containing transition metal oxides and phosphates in lithium-ion secondary batteries, and optimizing the distribution of zirconium and silicon elements, the problem of low power density of lithium-ion secondary batteries in the prior art is solved, and higher power density and better high-temperature performance are achieved.

CN119852484AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411523504.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-04-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

When the existing lithium-ion secondary batteries use lithium-containing transition metal oxides as the positive electrode active material, the power density is low.

Method used

The positive electrode active material containing lithium-containing transition metal oxide and lithium-containing transition metal phosphate is used, and the porosity of the positive electrode sheet and the composition of the electrode material are optimized by adjusting the distribution of zirconium elements and doping of silicon elements.

Benefits of technology

The power density of lithium-ion secondary batteries is significantly improved, and the circulation and storage performance are improved under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852484A_ABST
    Figure CN119852484A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion secondary battery and an electric device. Particularly, the invention provides a lithium ion secondary battery, which is characterized in that the lithium ion secondary battery comprises a positive pole piece, the positive pole piece comprises a positive current collector and a positive film layer which is arranged on the positive current collector and comprises a positive active material, the positive electrode active material comprises a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate, and the lithium-containing transition metal oxide comprises a nickel element, a cobalt element, a manganese element and / or an aluminum element and a zirconium element; the content of a zirconium element in a core area corresponding to the part, extending to 1 / 2 radius from the center of a primary particle of the lithium-containing transition metal oxide to the surface, of the lithium-containing transition metal oxide accounts for 40%-60%, the lithium-containing transition metal phosphate comprises an iron element, and the lithium-containing transition metal phosphate comprises a secondary particle formed by agglomeration of the primary particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium-ion secondary battery and an electrical device. Background Art

[0002] Lithium-ion batteries have gradually become the mainstream choice in the portable electronic devices, electric vehicles and hybrid vehicles markets due to their advantages such as high energy density, long cycle life and no memory effect. Among various types of positive electrode active materials, lithium-containing transition metal oxides (such as ternary positive electrode materials, such as lithium nickel cobalt manganese oxide) are widely used due to their high discharge specific capacity. However, in the prior art, when lithium-containing transition metal oxides are used as positive electrode active materials for secondary batteries, the power density of the secondary batteries is low.

[0003] Therefore, it is necessary to provide a lithium ion secondary battery which includes a lithium-containing transition metal oxide as a positive electrode active material and has a higher power density. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and an object of the present application is to provide a lithium ion secondary battery and an electric power device having a high power density.

[0005] The inventors have discovered that the above objectives can be achieved by adopting the technical solution of the present application.

[0006] A first aspect of the present application provides a lithium ion secondary battery, characterized in that the lithium ion secondary battery comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector and comprising a positive electrode active material, wherein:

[0007] The positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate.

[0008] The lithium-containing transition metal oxide comprises nickel, cobalt, manganese and / or aluminum, and zirconium. The content of zirconium in the core region corresponding to the half radius extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface is 40%-60%.

[0009] The lithium-containing transition metal phosphate includes an iron element, and the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles.

[0010] The lithium-ion secondary battery of the present application has a higher power density.

[0011] In any embodiment, the positive electrode sheet has a porosity of 23%-27% as measured by a true density method.

[0012] When the positive electrode plate has a porosity of 23%-27% as measured by a true density method, the lithium-ion secondary battery of the present application has a relatively high power density.

[0013] In any embodiment, the mass concentration of zirconium element on the surface of the primary particles of the lithium-containing transition metal oxide is 0.1%-0.5%.

[0014] In any embodiment, the mass concentration of zirconium element at the center of the primary particle of the lithium-containing transition metal oxide is 0.1%-0.5%.

[0015] In any embodiment, the mass concentration ratio of silicon element at the surface of the primary particle of the lithium-containing transition metal oxide is greater than the mass concentration ratio of silicon element at the center of the primary particle.

[0016] When the mass concentration ratio of silicon element at the surface of the primary particle containing lithium transition metal oxide is greater than the mass concentration ratio of silicon element at the center of the primary particle, the lithium ion secondary battery of the present application has good high temperature cycle performance and high temperature storage performance.

[0017] In any embodiment, the mass concentration of silicon element on the surface of the primary particles of the lithium-containing transition metal oxide is 0.01%-0.2%.

[0018] In any embodiment, the mass concentration of silicon element at the center of the primary particle of the lithium-containing transition metal oxide is less than 0.05%.

[0019] In any embodiment, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 5 μm.

[0020] In any embodiment, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2 μm to 15 μm.

[0021] In any embodiment, the specific surface area of ​​the lithium-containing transition metal phosphate is 2 m 2 / g to 10m 2 / g.

[0022] In any embodiment, the lithium-containing transition metal phosphate has the formula Li m1 Fe x Mn r P y O j1 Q1 q1, wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤m1≤1.15, x>0, r≥0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j1≤4, and 0≤q1≤0.1.

[0023] In any embodiment, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c ) 1- d Zr d O j2 Q2 q2 , wherein Q2 includes one or more of Si, Ti, Nb, Al, P, Sr, W, B, Ba, Mg, Sn, Y, Na, S, N, F, Cl, Br and I, 0.6≤m2≤1.5, 0.3≤a≤0.7, 0.02≤b≤0.15, a+b+c=1, 0<d≤0.1, 1.8≤j2≤2, 0≤q2≤0.2, j2+q2=2.

[0024] In any embodiment, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 30:1.

[0025] The second aspect of the present application provides an electrical device, which includes the lithium-ion secondary battery described in the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0027] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0028] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0029] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0030] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0031] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0032] Figure 7 is a scanning electron microscope image of a lithium-containing transition metal oxide in one embodiment of the present application.

[0033] Figure 8 is a scanning electron microscope image of a lithium-containing transition metal phosphate in one embodiment of the present application.

[0034] Fig. 9 This is a scanning electron microscope image of a mixture of a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate in one embodiment of the present application.

[0035] Fig.10 This is an electron probe image of a lithium-containing transition metal oxide primary particle according to one embodiment of the present application.

[0036] Fig.11 4 is a Zr element distribution diagram of the lithium-containing transition metal oxide primary particles according to one embodiment of the present application.

[0037] Description of reference numerals:

[0038] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION

[0039] Hereinafter, the lithium-ion secondary battery of the present application, its preparation method and the embodiment of the electric device thereof are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0040] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0043] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0045] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0046] Lithium-ion batteries have gradually become the mainstream choice in the portable electronic devices, electric vehicles and hybrid vehicles markets due to their advantages such as high energy density, long cycle life and no memory effect. Among various types of positive electrode active materials, lithium-containing transition metal oxides (such as ternary positive electrode materials, such as lithium nickel cobalt manganese oxide) are widely used due to their high discharge specific capacity. However, in the prior art, when lithium-containing transition metal oxides are used as positive electrode active materials of secondary batteries, the power density of the secondary batteries is low. Therefore, it is necessary to provide a lithium-ion secondary battery, which contains lithium-containing transition metal oxides as positive electrode active materials and has a high power density.

[0047] Based on this, the present application proposes a technical solution to solve the above technical problems.

[0048] A first aspect of the present application provides a lithium ion secondary battery, characterized in that the lithium ion secondary battery comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector and comprising a positive electrode active material, wherein:

[0049] The positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate.

[0050] The lithium-containing transition metal oxide comprises nickel, cobalt, manganese and / or aluminum, and zirconium. The content of zirconium in the core region corresponding to the half radius extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface is 40%-60%.

[0051] The lithium-containing transition metal phosphate includes an iron element, and the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles.

[0052] In the positive electrode active material, the content of zirconium in the core area corresponding to the 1 / 2 radius extending from the center of the primary particle of the lithium transition metal oxide to the surface accounts for 40%-60%, which means that the zirconium element exists evenly inside the particle and the doping effect is good. Zirconium doping can stabilize the lattice structure and ensure the stability of the material structure at a high voltage of 4.5V; the positive electrode active material also includes a lithium-containing transition metal phosphate, and the lithium-containing transition metal phosphate includes iron and includes secondary particles formed by agglomeration of primary particles. Since the secondary particles have a smaller specific surface area, the particle size of the secondary particles is closer to that of the lithium-containing transition metal oxide, which is more conducive to matching large-scale industrial processing technology without deteriorating the slurry processing performance; in addition, the voltage of the lithium-containing transition metal oxide drops rapidly at low SOC, while the lithium-containing transition metal phosphate forms a small platform at low SOC. Therefore, by adding the lithium-containing transition metal phosphate, the voltage drop in the low SOC segment becomes slower as a whole, unlike when pure lithium-containing transition metal oxide is used, a large voltage drop directly occurs. Therefore, it is possible to delay the voltage drop rate at low SOC, improve the kinetic performance, and thus improve the power performance of the secondary battery.

[0053] Therefore, the lithium-ion secondary battery of the present application has a higher power density.

[0054] The lithium-containing transition metal oxide and the lithium-containing transition metal phosphate can be distinguished by any means known to those skilled in the art, such as by SEM and / or EDS.

[0055] Whether the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles can be determined by any means known to those skilled in the art, such as by SEM.

[0056] In the present application, the lithium-containing transition metal oxide is modified by Zr, and the modification may be specifically manifested as doping and / or coating. In some embodiments, the modification is manifested as doping.

[0057] In some embodiments, the positive electrode sheet has a porosity of 23%-27% as measured by a true density method.

[0058] When the positive electrode plate has a plate porosity of 23%-27% as measured by the true density method, the plate porosity is high, the wettability of the electrolyte is improved, and the electrolyte provides an ion conduction path for the material, improving the kinetic performance, thereby improving the power performance of the lithium-ion secondary battery. Therefore, the lithium-ion secondary battery of the present application has a higher power density.

[0059] In some embodiments, the positive electrode sheet has a porosity of 23.5% to 26.5% as measured by a true density method. In some embodiments, the positive electrode sheet has a porosity of 23.5% to 26% as measured by a true density method.

[0060] In some embodiments, the porosity of the positive electrode plate measured by the true density method is 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, or a range consisting of any two of the above values ​​or a value within the range.

[0061] When the positive electrode plate porosity measured by the true density method is 23.5%-26.5%, the lithium-ion secondary battery of the present application has a higher power density.

[0062] In some embodiments, the mass concentration ratio (CONC) of zirconium element on the surface of the primary particles of the lithium-containing transition metal oxide is 0.1%-0.5%.

[0063] In some embodiments, the CONC of zirconium element at the surface of the primary particle of the lithium-containing transition metal oxide is 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.32%, 0.34%, 0.36%, 0.38%, 0.40%, 0.42%, 0.44%, 0.46%, 0.48%, 0.50%, or a range consisting of any two of the above values ​​or a value in the range.

[0064] In some embodiments, the CONC of the zirconium element at the surface of the primary particles of the lithium-containing transition metal oxide is 0.15% to 0.45%.

[0065] When the CONC of the zirconium element at the surface of the primary particles of the lithium-containing transition metal oxide is 0.15%-0.45%, the lithium-ion secondary battery of the present application has good high-temperature cycle and storage performance.

[0066] In some embodiments, the CONC of zirconium at the center of the primary particle of the lithium-containing transition metal oxide is 0.1%-0.5%. In some embodiments, the CONC of zirconium at the center of the primary particle of the lithium-containing transition metal oxide is 0.15%-0.45%. In some embodiments, the CONC of zirconium at the center of the primary particle of the lithium-containing transition metal oxide is 0.20%-0.40%.

[0067] In some embodiments, the CONC of Zr in the center of the primary particle of the lithium-containing transition metal oxide is 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.32%, 0.34%, 0.36%, 0.38%, 0.40%, 0.42%, 0.44%, 0.46%, 0.48%, 0.50%, or a range consisting of any two of the above values ​​or a value in the range.

[0068] In some embodiments, the mass concentration ratio of silicon element at the surface of the primary particle of the lithium-containing transition metal oxide is greater than the mass concentration ratio of silicon element at the center of the primary particle.

[0069] When the mass concentration of silicon at the surface of the primary particles of lithium-containing transition metal oxides is greater than the mass concentration of silicon at the center of the primary particles, Si is enriched on the surface of the material particles. The inert coating can alleviate the side reactions at the positive electrode interface and ensure that the material structure is not damaged under high voltage (~4.5V), so that the secondary battery has better high-temperature cycle performance and high-temperature storage performance.

[0070] In the present application, the lithium-containing transition metal oxide is modified by Si, and the modification may be specifically manifested as doping and / or coating. In some embodiments, the modification is manifested as coating.

[0071] In some embodiments, the mass concentration of silicon on the surface of the primary particles of the lithium-containing transition metal oxide is 0.01%-0.2%. In some embodiments, the mass concentration of silicon on the surface of the primary particles of the lithium-containing transition metal oxide is 0.05%-0.15%.

[0072] In some embodiments, the mass concentration of silicon element at the surface of primary particles of lithium transition metal oxide is 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.10%, 0.12%, 0.14%, 0.16%, 0.18%, 0.20%, or a range consisting of any two of the above values ​​or a value within the range.

[0073] When the mass concentration of silicon element at the surface of the primary particles of the lithium-containing transition metal oxide is 0.05%-0.15%, the lithium-ion secondary battery of the present application has good high-temperature storage performance.

[0074] In some embodiments, the mass concentration of silicon at the center of the primary particle of the lithium-containing transition metal oxide is less than 0.05%. In some embodiments, the mass concentration of silicon at the center of the primary particle of the lithium-containing transition metal oxide is 0%-0.02%.

[0075] In some embodiments, the CONC of Si at the center of the primary particle of the lithium-containing transition metal oxide is 0%, 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045%, or a range consisting of any two of the above values ​​or a value within the range.

[0076] When the mass concentration of silicon element at the center of the primary particle containing lithium transition metal oxide is 0%-0.02%, the lithium ion secondary battery of the present application has good high-temperature storage performance.

[0077] In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 5 μm. In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 2 μm to 3 μm. In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 3 μm. In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1.5 μm to 2.5 μm.

[0078] In some embodiments, the average particle size of the primary particles of the lithium transition metal oxide is 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm. , 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5μm, or a range consisting of any two of the above values ​​or a value in that range.

[0079] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal oxide is 2 μm to 10 μm. In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal oxide is 3 μm to 6 μm.

[0080] In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 10 nm to 1000 nm. In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 50 nm to 500 nm. In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 100 nm to 300 nm.

[0081] In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, or a range consisting of any two of the above values ​​or a value in the range.

[0082] The primary particles of lithium-containing transition metal phosphates are nanometer-sized, with a small average particle size, a short lithium ion transmission path, a fast transmission speed, and good kinetic performance. Including such lithium-containing transition metal phosphates in the positive electrode active material enables the secondary battery to have good power performance. In addition, the cost of lithium-containing transition metal phosphates is relatively low, so it can also reduce costs and is more suitable for commercial production and application.

[0083] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2 μm to 15 μm. In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 6 μm to 15 μm. In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 6.5 μm to 12 μm.

[0084] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, or a range consisting of any two of the above values ​​or a value in the range.

[0085] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is from 2 μm to 10 μm.

[0086] When the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2 μm to 10 μm, the lithium-ion secondary battery of the present application has a higher power density.

[0087] In some embodiments, the specific surface area of ​​the lithium-containing transition metal phosphate is 2 m 2 / g to 10m 2 In some embodiments, the specific surface area of ​​the lithium-containing transition metal phosphate is 7 m 2 / g to 9.5m 2 In some embodiments, the specific surface area of ​​the lithium-containing transition metal phosphate is 7 m 2 / g to 9m 2 / g.

[0088] In some embodiments, the specific surface area of ​​the lithium-containing transition metal phosphate is 2 m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.3m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g, or a range consisting of any two of the above values ​​or a value within the range.

[0089] In some embodiments, the lithium-containing transition metal phosphate has the formula Li m1 Fe x Mn r P y O j1 Q1 q1, wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤m1≤1.15, x>0, r≥0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j1≤4, and 0≤q1≤0.1.

[0090] In some embodiments, the lithium-containing transition metal phosphate has the formula Li m1 Fe x Mn r P y O j1 Q1 q1 , where m1 can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, and r can be 0, 0.05, 0. 1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, y can be 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, j1 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, q1 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.

[0091] In some embodiments, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c ) 1- d Zr d O j2 Q2 q2 , wherein Q2 includes one or more of Si, Ti, Nb, Al, P, Sr, W, B, Ba, Mg, Sn, Y, Na, S, N, F, Cl, Br and I, 0.6≤m2≤1.5, 0.3≤a≤0.7, 0.02≤b≤0.15, a+b+c=1, 0<d≤0.1, 1.8≤j2≤2, 0≤q2≤0.2, j2+q2=2.

[0092] In some embodiments, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c )1- d Zr d O j2 Q2 q2 , wherein Q2 includes one or more of Si, Ti, Nb, Al, P, and F.

[0093] In some embodiments, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c ) 1- d Zr d O j2 Q2 q2 , where m2 can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, 1.18, 1.20, 1.23, 1.25, 1.28, 1.30, 1.33, 1.35, 1.38, 1.40, 1.43, 1.45, 1.48, 1.50, a can be 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, b can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.1 4, 0.15, d can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, j2 can be 1.8, 1.81, 1.82, 1.83, 1.84, 1.85, 1.86, 1.87, 1.88, 1.89, 1.9, 1.91, 1.92, 1.93, 1. 94, 1.95, 1.96, 1.97, 1.98, 1.99, 2, q2 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2.

[0094] In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2: 1 to 30: 1. In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 3: 1 to 20: 1. In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 4: 1 to 19: 1.

[0095] In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, or a range consisting of any two of the above values ​​or a value within the range.

[0096] In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 9:1.

[0097] When the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 9:1, the lithium-ion secondary battery of the present application has a higher power density.

[0098] In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 9:1 to 30:1.

[0099] When the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 9:1 to 30:1, the lithium-ion secondary battery of the present application has good cycle performance and high-temperature storage performance.

[0100] The second aspect of the present application provides an electrical device, which includes the secondary battery described in the first aspect of the present application.

[0101] In addition, the lithium ion secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0102] In one embodiment of the present application, a secondary battery is provided.

[0103] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0104] [Positive electrode]

[0105] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0106] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0107] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0108] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0109] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0110] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0111] [Negative electrode]

[0112] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0113] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0114] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0115] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0116] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0117] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0118] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0119] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0120] [Electrolytes]

[0121] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0122] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0123] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0124] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0125] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0126] [Isolation film]

[0127] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0128] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0129] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0130] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0131] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0132] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0133] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0134] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0135] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0136] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0137] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0138] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0139] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0140] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0141] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0142] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0143] Example

[0144] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0145] 1. Preparation method

[0146] Example 1

[0147] (1) Preparation of positive electrode sheet:

[0148] Nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O) and manganese sulfate (MnSO4·H2O) were added into a continuous stirred tank reactor at a molar ratio of Ni:Co:Mn=55:12:33, deionized water was added to prepare a transition metal salt solution with a total molar concentration of 2 mol / L, 4 mol / L sodium hydroxide was added as a precipitant, and 0.4 mol / L ammonia water was added as a complexing agent. The precursor Ni of the ternary cathode material was prepared by coprecipitation reaction at pH 11.2 for 24 hours. 0.55 Co 0.12 Mn 0.33 (OH)2.

[0149] First, weigh the above precursor Ni according to the molar ratio of Li: (Ni + Co + Mn) = 1.06:1 0.55 Co 0.12 Mn 0.33 (OH)2 and lithium carbonate (Li2CO3), add 2500ppm ZrO2 and place in a high-speed mixer for mixing, then place in a kiln for sintering at 900℃ for 8h, cool to room temperature and grind by air flow mill for 5 hours to obtain the final product of lithium transition metal oxide. The content of zirconium element in the core area corresponding to the radius of 1 / 2 from the center of the primary particle of lithium transition metal oxide to the surface accounts for 53.10%, the CONC of zirconium element at the surface of the primary particle of lithium transition metal oxide ("CONC-surface-Zr") is 0.19%, and the CONC of zirconium element at the center of the primary particle ("CONC-center-Zr") is 0.20%; the CONC of silicon element at the surface of the primary particle of lithium transition metal oxide ("CONC-surface-Si") is 0, and the CONC of silicon element at the center of the primary particle ("CONC-center-Si") is 0; the average particle size of the primary particle of lithium transition metal oxide is 2.4μm, and the volume average particle size Dv50 is 4.5μm.

[0150] Iron phosphate and lithium carbonate are used as raw materials, and glucose and polyethylene glycol are added as carbon sources, and the mass of the carbon source accounts for 17% of the total mass of the raw materials. The above raw materials are mixed in a ratio of 3.85:1:1 and wet-ground with water as the solvent. The obtained slurry is spray-dried and then sintered in a roller furnace at 760°C for 24 hours. Nitrogen is introduced during the sintering process. Then the material is naturally cooled to a temperature of less than 80°C and then discharged to obtain a calcined material. The calcined material is subjected to air flow crushing, screening, demagnetization, and vacuum packaging. The frequency of the classifier of the air flow crushing is controlled to be 50-10080Hz and the frequency of the induced draft fan is controlled to be 20-5040Hz, and the average particle size of the primary particles is 200nm, the volume average particle size Dv50 is 8.6μm, and the BET is 8.1m 2 / g of lithium-containing transition metal phosphate.

[0151] The lithium-containing transition metal oxide and the lithium-containing transition metal phosphate are uniformly mixed in a mass ratio of 90:10 to obtain a positive electrode active material; the positive electrode active material, conductive carbon black SP and binder PVDF are dispersed in a solvent NMP in a mass ratio of 95:4:1 and mixed uniformly to obtain a positive electrode slurry; the positive electrode slurry is coated with a double-sided double-control coating device at a rate of 0.24 g / 1540.25 mm 2 The positive electrode sheet is evenly coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain the positive electrode sheet. The porosity of the positive electrode sheet is 24.2%.

[0152] (2) Preparation of negative electrode sheet:

[0153] The negative electrode active material graphite, the thickener sodium carboxymethyl cellulose, the binder styrene butadiene rubber, and the conductive agent acetylene black were mixed in a mass ratio of 95:2:2:1, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was stirred at 0.16 g / 1540.25 mm 2 Evenly coat the copper foil; after drying the copper foil at room temperature, transfer it to a 120°C oven and dry it for 1 hour, then cold press and cut it to obtain the negative electrode sheet.

[0154] (3) Isolation film:

[0155] 12μm thick polypropylene separator.

[0156] (4) Electrolyte:

[0157] 1 mol / L lithium hexafluorophosphate (LiPF6) was dissolved in a mixed system of ethylene carbonate (EC) + diethyl carbonate (DEC) + ethyl methyl carbonate (EMC) (20:20:60).

[0158] (5) Preparation of batteries:

[0159] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets to isolate them, and then wound to obtain a bare cell. The bare cell is placed in an aluminum-plastic film, and a lithium-ion battery is obtained after packaging, liquid injection, formation, and capacity division.

[0160] Example 2

[0161] (1) Preparation of positive electrode sheet:

[0162] Nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O) and manganese sulfate (MnSO4·H2O) were added into a continuous stirred tank reactor at a molar ratio of Ni:Co:Mn=55:12:33, deionized water was added to prepare a transition metal salt solution with a total molar concentration of 2 mol / L, 4 mol / L sodium hydroxide was added as a precipitant, and 0.4 mol / L ammonia water was added as a complexing agent. The precursor Ni of the ternary cathode material was prepared by coprecipitation reaction at pH 11.2 for 24 hours. 0.55 Co 0.12 Mn 0.33 (OH)2.

[0163] First, weigh the above precursor Ni according to the molar ratio of Li: (Ni + Co + Mn) = 1.06:1 0.55 Co 0.12 Mn 0.33 (OH)2 and lithium carbonate (Li2CO3), add 2500ppm ZrO2 and mix in a high-speed mixer, then place in a kiln for sintering at 900℃ for 8h, cool to room temperature and grind by jet mill for 5h to obtain intermediate product A1. The mixture of intermediate product A1 and 1500ppm SiO2 is placed in a high-speed mixer for mixing, then placed in a kiln for sintering at 500℃ for 4h to obtain the final product of lithium-containing transition metal oxide. The content of zirconium in the core area corresponding to the 1 / 2 radius extending from the center of the primary particle of the lithium transition metal oxide to the surface is 53.50%, the CONC of zirconium at the surface of the primary particle of the lithium transition metal oxide is 0.18%, and the CONC of zirconium at the center of the primary particle is 0.21%; the CONC of silicon at the surface of the primary particle of the lithium transition metal oxide is 0.11%, and the CONC of silicon at the center of the primary particle is 0.01%; the average particle size of the primary particles of the lithium transition metal oxide is 2.4μm, and the volume average particle size Dv50 is 4.5μm.

[0164] Iron phosphate and lithium carbonate are used as raw materials, and glucose and polyethylene glycol are added as carbon sources, and the mass of the carbon source accounts for 17% of the total mass of the raw materials. The above raw materials are mixed in a ratio of 3.85:1:1 and wet-ground with water as the solvent. The obtained slurry is spray-dried and then sintered in a roller furnace at 760°C for 24 hours. Nitrogen is introduced during the sintering process. Then the material is naturally cooled to a temperature of less than 80°C and then discharged to obtain a calcined material. The calcined material is subjected to air flow crushing, screening, demagnetization, and vacuum packaging. The frequency of the classifier of the air flow crushing is controlled to be 50-10080Hz and the frequency of the induced draft fan is controlled to be 20-5040Hz, and the average particle size of the primary particles is 200nm, the volume average particle size Dv50 is 8.6μm, and the BET is 8.1m 2 / g of lithium-containing transition metal phosphate.

[0165] The lithium-containing transition metal oxide and the lithium-containing transition metal phosphate are uniformly mixed in a mass ratio of 90:10 to obtain a positive electrode active material; the positive electrode active material, conductive carbon black SP and binder PVDF are dispersed in a solvent NMP in a mass ratio of 95:4:1 and mixed uniformly to obtain a positive electrode slurry; the positive electrode slurry is coated with a double-sided double-control coating device at a rate of 0.24 g / 1540.25 mm 2 The positive electrode sheet is uniformly coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain the positive electrode sheet. The porosity of the positive electrode sheet is 24.3%.

[0166] (2) Preparation of negative electrode sheet:

[0167] Same as in Example 1.

[0168] (3) Isolation film:

[0169] Same as in Example 1.

[0170] (4) Electrolyte:

[0171] Same as in Example 1.

[0172] (5) Preparation of batteries:

[0173] Same as in Example 1.

[0174] Embodiment 3-6

[0175] Compared with Example 1, the main differences of Example 3 are shown in Table 1.

[0176] Comparative Example 1

[0177] Compared with Example 2, Comparative Example 1 is different mainly in that the positive electrode active material does not contain lithium-containing transition metal phosphate, and the porosity of the positive electrode sheet is 22.5%.

[0178] Comparative Example 2

[0179] Compared with Example 2, the main difference between Comparative Example 1 is that ZrO2 and SiO2 are not used in the preparation process of the lithium-containing transition metal oxide, so that the CONC of the zirconium element at the surface of the primary particles of the lithium-containing transition metal oxide is 0, and the CONC of the zirconium element at the center of the primary particles is 0; the CONC of the silicon element at the surface of the primary particles of the lithium-containing transition metal oxide is 0, and the CONC of the silicon element at the center of the primary particles is 0.

[0180] 2. Test Method

[0181] 1. The content ratio of zirconium in the core area corresponding to 1 / 2 radius extending from the center of the primary particle to the surface

[0182] The powder samples were prepared into electron microscope samples by resin embedding and thick ion polishing, and carbon spraying was performed before testing to increase the conductivity of the material. The particles with good flatness and polishing were selected and the electron probe (EPMA) line scanning analysis was performed by drawing a line at the center of the particles to obtain the cumulative distribution of the Zr element quantity in the entire area of ​​the primary particle line scan. The proportion of the cumulative Zr element quantity in the core area corresponding to the 1 / 2 radius extending from the center of the primary particle to the surface to the cumulative Zr element quantity in the entire area is the obtained content proportion.

[0183] 2. Mass concentration ratio of zirconium element on the surface of primary particles

[0184] The powder samples were prepared into electron microscope samples by resin embedding and thick ion polishing, and carbon spraying was performed before testing to increase the conductivity of the material. The particles with good flatness and polishing were selected and the electron probe (EPMA) line scanning analysis was performed by drawing a line in the center of the particles, and finally the mass concentration ratio of zirconium element at the surface of the primary particles was obtained.

[0185] 3. Mass concentration ratio of zirconium element at the center of primary particles

[0186] The powder samples were prepared into electron microscope samples by resin embedding and thick ion polishing, and carbon spraying was performed before testing to increase the conductivity of the material. The particles with good flatness and polishing were selected and the electron probe (EPMA) line scanning analysis was performed at the center of the particles to finally obtain the mass concentration ratio of zirconium element at the center of the primary particle.

[0187] 4. Mass concentration of silicon on the surface of primary particles

[0188] The powder samples were prepared into electron microscope samples by resin embedding and thick ion polishing, and carbon spraying was performed before testing to increase the conductivity of the material. The particles with good flatness and polishing were selected and the electron probe (EPMA) line scanning analysis was performed by drawing a line in the center of the particles, and finally the mass concentration ratio of silicon element at the surface of the primary particles was obtained.

[0189] 5. Mass concentration ratio of silicon element at the center of primary particles

[0190] The powder samples were prepared into electron microscope samples by resin embedding and thick ion polishing, and carbon spraying was performed before testing to increase the conductivity of the material. The particles with good flatness and polishing were selected and the electron probe (EPMA) line scanning analysis was performed at the center of the particles to finally obtain the mass concentration ratio of silicon element at the center of the primary particle.

[0191] 6. Average particle size of primary particles

[0192] The software "LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System" is used to automatically identify the primary particles by AI, draw the particle outline, and obtain the particle quantity, number, area, and maximum caliper diameter. 2,000 particles are taken and the average is calculated.

[0193] Average primary particle size = sum of all measured particle sizes (longest diameter) / sum of all measured particle numbers.

[0194] 7. Volume average particle size Dv50

[0195] Malvern MasterSizer 3000 laser particle size analyzer was used to measure the particle size according to the standard procedure: GB / T19077-2016 / ISO 13320:2009. The specific test procedure is as follows: Take an appropriate amount of the sample to be tested, and ensure that the sample concentration is 8% to 12% shading. Add 20mL of deionized water, and ultrasonicate for 5 minutes at a frequency of 53KHz and a power of 120W to ensure that the sample is completely dispersed. Then, measure the sample according to the GB / T19077-2016 / ISO 13320:2009 standard.

[0196] 8. Specific surface area

[0197] Use a specific surface and pore analyzer and refer to the standard process: GB / T19587-2017 / ISO 9277:2010 for measurement. The specific test process is as follows: Use a special sample tube to take an appropriate amount of sample, heat and vacuum for 2 hours, and weigh the total weight after cooling to room temperature, and subtract the mass of the sample tube to obtain the sample mass. Load the sample tube into the workstation, and measure the adsorption amount of gas on the solid surface under different adsorption pressures at a constant low temperature. Based on the BET multilayer adsorption theory and its formula, the sample monolayer adsorption amount is obtained, thereby calculating the specific surface area of ​​the unit mass of the solid sample.

[0198] 9. Porosity of positive electrode sheet measured by true density method

[0199] The test was carried out with reference to the standard process GB / T 24586-2009. The specific test process is as follows: Use tweezers to select >20 discs with good appearance and no powder falling on the edges and put them into the sample cup. Record the number of discs and calculate the apparent volume. Then put the sample cup with the sample into the true density tester, close the test system, and introduce helium according to the program. By detecting the pressure of the gas in the sample chamber and the expansion chamber, the real volume is calculated according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested.

[0200] 10. 30S20% SOC power density

[0201] Place the battery in a constant temperature room at 25℃ and let it stand for 2h. When the battery temperature remains at 25℃, perform the following test. Charge to 4.5V with 1 / 3C current constant current, and continue constant voltage charging until the charging current is less than 0.05C and then cut off; pause for 30min; discharge to 0.8C0 (C0 is the battery capacity) with 1 / 3C current constant current, that is, adjust to 20% SOC, and let it stand for 2h. Discharge with X1 A current for 30S, record the capacity of this step as C1, let it stand for 5min, recharge C1 capacity with 1 / 20C current, discharge with X2 A current for 30S, record the capacity of this step as C2, let it stand for 5min, recharge C2 capacity with 1 / 20C current, repeat the above steps until the terminal voltage is 2.8±0.05V, at which time the current is Xn, and the power density is calculated with this current.

[0202] Power density = power (W) / discharge capacity (Wh) = discharge voltage (V) * test current (A) / discharge capacity (Wh)

[0203] 11. Cycle performance

[0204] Place the battery in a 45℃ constant temperature room and let it stand for 2 hours. When the battery temperature remains at 45℃, perform the charge and discharge test. Charge to 4.5V with 1 / 3C constant current, and continue constant voltage charging until the charging current is less than 0.05C, then stop; pause for 30 minutes; discharge to 2.8V with 1 / 3C constant current; pause for 10 minutes. The above is a charge and discharge cycle of the battery, which is repeated continuously until the battery capacity decays to 80% of the initial value, and the number of cycles is recorded.

[0205] 12. High temperature storage performance

[0206] At 25°C, the battery is charged to 4.5V at a constant current rate of 1 / 3C, then charged at a constant voltage until the current is less than or equal to 0.05C, and then discharged at a constant current rate of 1 / 3C to 2.8V after standing for 30 minutes. The initial discharge capacity of the battery is obtained by testing. After standing for 30 minutes, the battery is charged to 4.5V at a constant current rate of 1 / 3C, and then charged at a constant voltage until the current is less than or equal to 0.05C. After that, the fully charged battery is placed in a 60°C oven for storage for 100 days. The battery is taken out after 100 days of high-temperature storage, and the temperature is naturally lowered to 25°C, and discharged at a constant current rate of 1 / 3C to 2.8V, then charged at a constant current rate of 1 / 3C to 4.5V, and then charged at a constant voltage until the current is less than or equal to 0.05C, and then discharged at a constant current rate of 1 / 3C to 2.8V. The discharge capacity of the battery after 100 days of high-temperature storage is obtained by testing.

[0207] Capacity retention rate (%) of the battery after 100 days of high-temperature storage = discharge capacity after 100 days of high-temperature storage / initial discharge capacity×100%.

[0208] III. Analysis of test results of various embodiments and comparative examples

[0209] The lithium-ion batteries of the embodiments and comparative examples were prepared according to the above method, and various parameters were measured. The relevant parameters of the positive electrode active material and the positive electrode sheet are shown in Table 1, and the performance test results of the secondary battery are shown in Table 2.

[0210] Table 1: Related parameters of positive electrode active materials and positive electrode sheets

[0211]

[0212] Table 2: Performance test results of secondary batteries

[0213]

[0214] According to the above results, the secondary batteries in Examples 1-6 all include a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector and including a positive electrode active material, wherein the positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate, the lithium-containing transition metal oxide includes nickel, cobalt, manganese and / or aluminum, and zirconium, the content of zirconium in the core region corresponding to the radius extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface to 1 / 2 is 40%-60%, the lithium-containing transition metal phosphate includes iron, and the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles. From the comparison of Examples 1-6 and Comparative Examples 1-2, it can be seen that the lithium-ion secondary battery of the embodiment of the present application has a higher power density.

[0215] The lithium-containing transition metal oxide of Example 1 was observed using a ZEISS sigma 300 scanning electron microscope. The observation results are shown in Figure 7 The lithium-containing transition metal phosphate of Example 1 was observed using a ZEISS sigma 300 scanning electron microscope. The observation results are shown in Figure 8 The lithium-containing transition metal oxide of Example 1 and the lithium-containing transition metal phosphate were mixed and observed using a ZEISS sigma 300 scanning electron microscope. The observation results are shown in Fig. 9 .

[0216] The lithium-containing transition metal oxide powder sample of Example 1 was prepared into an electron microscope sample by resin embedding and ion polishing, and carbon spraying was performed to increase the conductivity of the material. The particles with good flatness and polishing were selected. Fig.10 EPMA image of primary particles of lithium-containing transition metal oxides, and the lines are EPMA line scan areas.

[0217] The lithium-containing transition metal oxide powder sample of Example 1 was prepared into an electron microscope sample by resin embedding and thick ion polishing, and carbon spraying was performed to increase the conductivity of the material. The particles with good flatness and polishing were selected, and the EPMA line scanning analysis was performed by drawing a line at the center of the particles. The analysis results are shown in Fig.11 , which shows the distribution of Zr element in the line scan area of ​​the primary particle of lithium-containing transition metal oxide, that is, the mass concentration ratio (CONC) of Zr at different positions in the particle.

[0218] From the comparison between Examples 1-4 and 6 and Example 5, it can be seen that when the porosity of the positive electrode plate measured by the true density method is 23.5%-26.5%, the lithium-ion secondary battery of the embodiment of the present application has a higher power density.

[0219] From the comparison between Examples 2, 5-6 and Examples 1, 3-4, it can be seen that when the mass concentration ratio of silicon element at the surface of the primary particles containing lithium transition metal oxide is greater than the mass concentration ratio of silicon element at the center of the primary particles, the lithium-ion secondary battery of the embodiments of the present application has better high-temperature cycle performance and high-temperature storage performance.

[0220] From the comparison between Examples 1-2, 4, 6 and Examples 3 and 5, it can be seen that when the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 9:1, the lithium-ion secondary battery of the present embodiment has a higher power density.

[0221] From the comparison between Examples 1 and 3 and Example 4, and between Examples 2 and 5 and Example 6, it can be seen that when the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 9:1 to 30:1, the lithium-ion secondary battery of the embodiment of the present application has good cycle performance and high temperature storage performance.

[0222] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector and comprising a positive electrode active material, wherein: The positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate. The lithium-containing transition metal oxide comprises nickel, cobalt, manganese and / or aluminum, and zirconium. The content of zirconium in the core region corresponding to the half radius extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface is 40%-60%. The lithium-containing transition metal phosphate includes an iron element, and the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles.

2. The lithium ion secondary battery according to claim 1, wherein The positive electrode plate has a porosity of 23%-27% as measured by a true density method.

3. The lithium ion secondary battery according to claim 1 or 2, wherein: The mass concentration of zirconium element on the surface of the primary particles of the lithium-containing transition metal oxide is 0.1%-0.5%.

4. The lithium ion secondary battery according to any one of claims 1 to 3, wherein The mass concentration of zirconium element at the center of the primary particle of the lithium-containing transition metal oxide is 0.1%-0.5%.

5. The lithium ion secondary battery according to any one of claims 1 to 4, wherein The mass concentration ratio of silicon element at the surface of the primary particle of the lithium-containing transition metal oxide is greater than the mass concentration ratio of silicon element at the center of the primary particle.

6. The lithium ion secondary battery according to any one of claims 1 to 5, wherein: The mass concentration of silicon element on the surface of the primary particles of the lithium-containing transition metal oxide is 0.01%-0.2%.

7. The lithium ion secondary battery according to any one of claims 1 to 6, wherein: The mass concentration of silicon element at the center of the primary particle of the lithium-containing transition metal oxide is less than 0.05%.

8. The lithium ion secondary battery according to any one of claims 1 to 7, wherein: The average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 5 μm.

9. The lithium ion secondary battery according to any one of claims 1 to 8, wherein: The volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2 μm to 15 μm.

10. The lithium ion secondary battery according to any one of claims 1 to 9, wherein: The specific surface area of ​​the lithium-containing transition metal phosphate is 2 m 2 / g to 10m 2 / g.

11. The lithium ion secondary battery according to any one of claims 1 to 10, wherein: The lithium-containing transition metal phosphate has a molecular formula of Li m1 Fe x Mn r P y O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤m1≤1.15, x>0, r≥0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j1≤4, and 0≤q1≤0.

1.

12. The lithium ion secondary battery according to any one of claims 1 to 11, wherein: The lithium-containing transition metal oxide has a molecular formula of Li m2 (Ni a Co b Mn c ) 1-d Zr d O j2 Q2 q2 , wherein Q2 includes one or more of Si, Ti, Nb, Al, P, Sr, W, B, Ba, Mg, Sn, Y, Na, S, N, F, Cl, Br and I, 0.6≤m2≤1.5, 0.3≤a≤0.7, 0.02≤b≤0.15, a+b+c=1, 0<d≤0.1, 1.8≤j2≤2, 0≤q2≤0.2, j2+q2=2.

13. The lithium ion secondary battery according to any one of claims 1 to 12, wherein: The mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 30:

1.

14. An electrical device comprising the lithium ion secondary battery according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Cathode active material for lithium secondary battery, production method therefor, cathode comprising same for lithium secondary battery, and lithium secondary battery comprising same

    CN112005411A

  • Secondary battery and preparation method thereof, and battery module, battery pack and device comprising secondary battery

    CN114982002A

  • High-nickel positive electrode material, preparation method thereof and lithium ion battery

    CN116826049A

  • Nonaqueous secondary battery

    JP2012043814A

  • Positive electrode material for nonaqueous secondary battery and manufacturing method thereof, and positive electrode for nonaqueous secondary battery using positive electrode material for nonaqueous secondary battery and nonaqueous secondary battery using the same

    JP2016096075A

Cited By

  • Battery monomer, battery device, power utilization device and energy storage device

    CN122314858A

  • Battery cell, battery device, power consuming device, and energy storage device

    CN122314858B

  • Battery monomer, battery device, power utilization device and energy storage device

    CN122337993A